Effect of boron-containing additives on rheological properties of asphalt binder. Issue 4 (1st October 2016) - Oruç, Şeref; Yılmaz, Bahadır; Sancak, Kemal
Abstract : In this study, four novel boron-containing additives were synthesised chemically in the laboratory. The modification was performed by adding the additives, respectively, into asphalt at a certain amount by weight at the same temperature and mixing conditions. The modification mechanism and microstructure of the blends were characterised by Fourier transform infrared spectrometer and scanning electron microscopy. The variation in modified samples in comparison to base asphalt was investigated by performing the penetration, softening point, dynamic shear rheometer, amplitude–frequency–temperature sweeps and rotational viscosity tests. It was observed that the additives increased the softening point, rutting resistance, elastic properties and viscosity of asphalt. The additive synthesised with triazole borate ester octanol-sulphuric acid catalysts gave the most enhancements, relative to base asphalt.